2019
DOI: 10.1002/chem.201900296
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of Dithienocyclopentapyrene‐Based Non‐Fullerene Electron Acceptors: Configuration Effect on Photoelectronic Properties

Abstract: One pair of isomers, centrosymmetric anti‐Py‐1 and axisymmetric syn‐Py‐2, was designed and synthesized with an acceptor–donor–acceptor (A–D–A) structure by choosing dithienocyclopentapyrene with four 4‐hexylphenyl side chains as the D unit, and 2‐(5,6‐difluoro‐3‐oxo‐2,3‐dihydro‐1H‐inden‐1‐ylidene) malononitrile as the A unit. In‐depth structure–property relationship studies revealed that the isomers have similar UV/Vis absorption, fluorescence emission, and energy levels but significant differences in molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For instance, Huang and co‐workers utilized dithienocyclopentapyrene with 4‐hexylphenyl side chains as the central donor unit and IC2F moieties as the acceptor unit to synthesize a pair of syn/anti isomers, Py‐1 and Py‐2, which exhibited nearly identical energy levels, UV–vis absorption, and fluorescence emission. [ 112 ] According to the DFT calculations, the syn/anti isomerization changes the electrostatic potential and the molecular dipole moment, which in turn significantly influences its surface energy. Compared with the PTB7‐Th:Py‐2 blend, the PTB7‐Th:Py‐1 blend film showed better phase separation, and exhibited higher and more balanced hole/electron mobilities.…”
Section: Isomeric A–d–a‐type Nonfullerene Smasmentioning
confidence: 99%
“…For instance, Huang and co‐workers utilized dithienocyclopentapyrene with 4‐hexylphenyl side chains as the central donor unit and IC2F moieties as the acceptor unit to synthesize a pair of syn/anti isomers, Py‐1 and Py‐2, which exhibited nearly identical energy levels, UV–vis absorption, and fluorescence emission. [ 112 ] According to the DFT calculations, the syn/anti isomerization changes the electrostatic potential and the molecular dipole moment, which in turn significantly influences its surface energy. Compared with the PTB7‐Th:Py‐2 blend, the PTB7‐Th:Py‐1 blend film showed better phase separation, and exhibited higher and more balanced hole/electron mobilities.…”
Section: Isomeric A–d–a‐type Nonfullerene Smasmentioning
confidence: 99%
“…developed configurational anti-and syn-isomers of dithienocyclopentapyrene-based NFAs, whereas the anti-isomer exhibited higher and more balanced hole/electron mobilities and thus better photovoltaic performance than the syn-isomer (6.07% vs 3.07%). 54 All these results could inspire furthermore exploration of such isomeric effects on their photoelectronic properties.…”
Section: Introductionmentioning
confidence: 94%
“…Meanwhile when recalling the common isomeric phenomena in organic electronics, it is well-known that isomerization has a significant effect on the thermal-, optical-, and electrochemical-properties, charge carrier mobility, and eventually device performance. Very recently, the constitutional isomeric effects of NFAs just have been investigated, among which Zhan et al revealed that a NFA FNIC2 based on a thieno­[3,2- b ]­thiophene-fused benzo­[1,2- b :4,5- b′ ]­dithiophene core showed a red-shifted absorption, higher crystallinity, optimized morphology, and higher PCE of 13.0% than its isomer analogue FNIC1 (10.3%) . Huang et al developed configurational anti- and syn-isomers of dithienocyclopentapyrene-based NFAs, whereas the anti-isomer exhibited higher and more balanced hole/electron mobilities and thus better photovoltaic performance than the syn-isomer (6.07% vs 3.07%) . All these results could inspire furthermore exploration of such isomeric effects on their photoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The molecules 8-46 (Py-1) and 8-47 (Py-2) bear a dithienocyclopentapyrene core and INCN-2F acceptor groups, whereby 8-46 is the centrosymmetric and 8-47 the axisymmetric isomer . While the optical band gap ( 8-46 , 1.95 eV; 8-47 , 1.97 eV) and the energy levels show no significant difference, the centrosymmetric isomer shows a significantly higher electron mobility in the blend with PTB7-Th, which also results in an increased PCE of 5.75% (compared to 3.47% for a PTB7-Th/ 8-47 -based solar cell) …”
Section: Eight Fused Aromatic Ring Systemsmentioning
confidence: 99%